Does the Knowledge Sharing Self-Efficacy Moderate the Relationship between Knowledge Collecting Behavior and Social Networking? - Sarah Khan (UW Journal of Management Sciences, 2021)
Purpose: Today, the biggest challenge most organizations are facing is how to make effective use of available social networking technologies for enhancing employees’ proficiency and productivity. That has recently gained considerable attention from organizations around the world that are encountering a pattern change in their overall business environment and specific operational requirements. The purpose of this study is to examine the direct impact of knowledge collecting behavior on employees’ productivity and an indirect effect through social networking technologies. Design and Methodology: The sample data were collected from employees working in service sector organizations located in Islamabad, Rawalpindi, and Wah Cantt, cities of the Northern Punjab region of Pakistan. Structural Equation Modelling technique using the Smart PLS software tool was applied to the data for statistical analysis. Findings: The results have shown that the hypothesis direct effect of knowledge collecting behavior and an indirect effect through knowledge sharing self-efficacy on social networking are significant. Furthermore, the self-efficacy factor proved to be a significant positive moderator in strengthening the direct relationship between knowledge collecting and social networking. Implications: The findings provided useful insight for policymakers in service sector organizations for planning effective use of social networking technologies and crafting knowledge collecting behavior among employees for achieving desired organizational outcomes. The study also identified useful future avenues for researchers to extend their studies on similar lines.